If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10c + 23 = 29 Reorder the terms: 23 + 10c = 29 Solving 23 + 10c = 29 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 10c = 29 + -23 Combine like terms: 23 + -23 = 0 0 + 10c = 29 + -23 10c = 29 + -23 Combine like terms: 29 + -23 = 6 10c = 6 Divide each side by '10'. c = 0.6 Simplifying c = 0.6
| 3(2y+9)=4y-71 | | (6y-4)=(5y-3) | | (7b+6)(5b+1)= | | (11x+8)=(8x+1) | | (2-i)z^2+2z+2+i=0 | | (3y+8)=(5y-14) | | -6x+6=14-2 | | b-13=20 | | (4x-7)=(2x+11) | | (6b+7)(3b-5)= | | 4(5x+3)=135 | | sen(5x)=2 | | 2+3=n+6n | | t-27=0.8 | | 8+7x=-2x+7 | | 4n=230 | | 10k+18=2(5k+8) | | 2x+110= | | 3(4g+38)-12g-114=0 | | (8x-3x^4-6x^3)= | | 160+50x=1450 | | 7x+4y=117 | | V^2-14v-27=0 | | m-5=9.4 | | 5p+9p=12 | | 4-ax=2 | | x^4-3x^2-3x= | | 4x+7y=74 | | (x^2+4x)(x^2+4x-17)+60=0 | | (x^4-6x^2+8x)= | | 5*-5=100 | | 68-4y+4y=24 |